2014
DOI: 10.1155/2014/730301
|View full text |Cite
|
Sign up to set email alerts
|

Human AP Endonuclease 1: A Potential Marker for the Prediction of Environmental Carcinogenesis Risk

Abstract: Human apurinic/apyrimidinic endonuclease 1 (APE1) functions mainly in DNA repair as an enzyme removing AP sites and in redox signaling as a coactivator of various transcription factors. Based on these multifunctions of APE1 within cells, numerous studies have reported that the alteration of APE1 could be a crucial factor in development of human diseases such as cancer and neurodegeneration. In fact, the study on the combination of an individual's genetic make-up with environmental factors (gene-environment int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 172 publications
(173 reference statements)
0
15
0
Order By: Relevance
“…The family of glycosylases involved in mitochondrial BER consists of several members: OGG1 that is able to remove the most common and the most mutagenic modification introduced to the mtDNA—8-oxo-dG [ 147 ]; UNG1, which is responsible for the removal of uracil, resulting from the spontaneous deamination of the cytosine [ 148 ]; NTH1-dichotomous enzyme, possessing glycosylase and AP lyase activities, that excises pyrimidine lesions (ThyGly, FapyG and FapyA) [ 149 ]; NEIL1 and NEIL2 that are also involved in the removal of FapyG and FapyA [ 150 ]; MYH, enzyme that detects adenine placed opposite to 8-oxo-dG [ 151 ]. After specific glycosylases have identified and extracted the damaged base, the abasic sites are resolved by APE endonuclease that prepares the DNA molecule for the Polγ mediated repair process by cleaving 3′-hydroxyl and 5′-deoxyribose-5-phosphate sites [ 152 ]. Afterwards, the newly synthesized section of DNA is ligated to the rest of the molecule by DNA ligase III.…”
Section: Aging and Mitochondrial Dna Repairmentioning
confidence: 99%
“…The family of glycosylases involved in mitochondrial BER consists of several members: OGG1 that is able to remove the most common and the most mutagenic modification introduced to the mtDNA—8-oxo-dG [ 147 ]; UNG1, which is responsible for the removal of uracil, resulting from the spontaneous deamination of the cytosine [ 148 ]; NTH1-dichotomous enzyme, possessing glycosylase and AP lyase activities, that excises pyrimidine lesions (ThyGly, FapyG and FapyA) [ 149 ]; NEIL1 and NEIL2 that are also involved in the removal of FapyG and FapyA [ 150 ]; MYH, enzyme that detects adenine placed opposite to 8-oxo-dG [ 151 ]. After specific glycosylases have identified and extracted the damaged base, the abasic sites are resolved by APE endonuclease that prepares the DNA molecule for the Polγ mediated repair process by cleaving 3′-hydroxyl and 5′-deoxyribose-5-phosphate sites [ 152 ]. Afterwards, the newly synthesized section of DNA is ligated to the rest of the molecule by DNA ligase III.…”
Section: Aging and Mitochondrial Dna Repairmentioning
confidence: 99%
“…Whenever a toxic modification on a specific nucleobase appears or leads to formation of abasic sites, base excision repair (BER) is activated to resolve this problem [16] . Key players of the BER are DNA glycosylases (uracil-DNA glycosylase (UNG) [17] , 8-oxoguanine DNA glycosylase (OGG1) [18] , n th endonuclease III-like 1 (NTHL1) [19] and nei endonuclease VIII-like 1, 2 or 3 (NEIL1/NEIL2/NEIL3) [20] ), all of which recognize different base modifications; DNA endonucleases such as apurinic/apyrimidinic endonuclease 1 (APE1) [21] ; DNA polymerases (Polβ) and DNA ligases (Lig1) [22] . Specificity of this repair pathway is achieved by activity of the glycosylases that scan DNA molecules by slightly pulling the nucleotide strain.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have also reported that the decline of major components (pol β , pol γ , APE1, and Sirt6) of BER pathway is associated with aging [ 84 89 ]. Interestingly, deficiency of APE1, a vital element of BER initiation, leads to telomere dysfunction and segregation, suggesting that BER plays a role in aging through telomere protection [ 90 , 91 ].…”
Section: Dna Repair and Longevitymentioning
confidence: 99%